(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to find out the Implementation of Slum Area Eradication Program in Letta Village, Bantaeng District, Bantaeng Regency. This study used qualitative research, the sources of data used primary and secondary, the number of informants was 7 people. Data collection technique used observation, interview and documentation. Data analysis techniques used data reduction steps, data presentation, qualitative data verification, and using triangulation of data validation namely triangulation of sources, techniques, and time. The results of this study showed that the Implementation of Slum Area Eradication Program in Letta Village, Bantaeng district, Bantaeng Regency had been realized optimally, seen from (1) the structured environment that had been realized; (2) the provision of family toilets that had not been realized so that there were still people who used latrines in the beach; (3) adequate supply of water was maximally realized.